ANALISIS TERMOGRAVIMETRI MIKROALGA SPIRULINA PLATENSIS DENGAN LAJU PEMANASAN 10ºC/MENIT - Claudia B. P, Chintya Zalza Laola; Subagyono, RR Dirgarini Julia Nurlianti; Kassim, Mohd Asyraf (PROSIDING SEMINAR KIMIA, 2024)
The pyrolysis of Spirulina platensis microalgae using thermogravimetric analysis at a heating rate of 10°C/min has been conducted. This study aims to examine the characteristics of Spirulina platensis microalgae through its thermal decomposition behavior and the active and passive pyrolysis temperature ranges in the microalgae powder. Based on the analysis results, Spirulina platensis microalgae contains 8.34% moisture and 7.18% ash content. The decomposition pattern of Spirulina platensis microalgae is divided into three stages: the water evaporation stage occurs at temperatures ≤ 150ºC, the active/main pyrolysis stage occurs in the temperature range of 150-502°C, and the passive pyrolysis stage occurs at temperatures ≥ 502°C. Keywords: Spirulina platensis, Pyrolysis, and Thermogravimetric Analysis.